A High Percentage of Patients Recovered From COVID-19 but Discharged With Abnormal Liver Function Tests - Gan, Qinyi; Gong, Beilei; Sun, Manli; Cao, Zhujun; Zheng, Yuyan; Zhang, Yajie; Wen, Pengfei; Shen, Yuanbing; Hong, Lei; Hou, Tingting; Jia, Yuqin; Li, Wei; et al. (Frontiers in Physiology, 2021)
Abstract Background: Coronavirus disease 2019 (COVID-19) pandemic has become the most severe global health issue. Abnormal liver functions are frequently reported in these patients. However, liver function abnormality was often overlooked during COVID-19 treatment, and data regarding liver functions after cure of COVID-19 is limited. This study aimed to reveal the changes of liver function tests (LFTs) during hospitalization, and its clinical significance in patients with COVID-19. Methods: In this retrospective, bi-center study, a total of 158 hospitalized patients diagnosed with COVID-19 in China were included from January 22nd, 2020 to February 20th, 2020. Clinical features, laboratory parameters including LFTs and treatment data were collected and analyzed. LFTs included alanine transaminase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (GGT) and total bilirubin (TB). Patients were considered with abnormal LFTs when any value of these tests was higher than upper limit of normal. Results: Of 158 patients with COVID-19, 67 (42.41%) patients had abnormal LFTs on admission and another 50 (31.65%) patients developed abnormal LFTs during hospitalization. The incidence of LFTs abnormality in severe COVID-19 cases was significantly higher than non-severe cases. All LFTs in COVID-19 patients were correlated with oxygenation index. There was no statistical difference in treatment between the patients with or without liver test abnormalities. By the time of discharge, there were still 64 (40.50%) patients with abnormal LFTs. Logistic regression analysis identified younger age, hypertension and low lymphocyte counts as independent risk factors for persistent abnormal LFTs during hospitalization. Conclusions: LFTs abnormality was common in COVID-19 patients and was more prevalent in severe cases than in non-severe cases. A substantial percentage of patients still had abnormal LFTs by the time of discharge.